Starch-based flocculant outperformed aluminium sulfate hydrate and polyaluminium chloride through effective bridging for harvesting acicular microalga Ankistrodesmus - Choy, Sook Yan; Prasad, Krishnamurthy Nagendra; Wu, Ta Yeong; Raghunandan, Mavinakere Eshwaraiah; Phang, Siew Moi; Juan, Joon Ching; Ramanan, Ramakrishnan Nagasundara (Elsevier, 2018)
Microalgae represent a diversified pool of resources famed for valuable raw materials which are favoured over terrestrial crops in certain applications. Even so, limited green microalgae strains have been explored and studied till date. Thus, the highlight of this study is to comparatively evaluate the performance of pH-induced settling, use of chemical coagulants and starches as natural coagulants for efficient harvesting of acicular-shaped Ankistrodesmus. Biomass recoveries were determined through conventional jar tests and small scale coagulation-flocculation studies. Increased acidity at pH 3 and enhanced basicity above pH 11.5 have facilitated self-flocculation of cells leading to rapid settling. Despite that, potential reduction in chlorophyll contents and contamination from resulting precipitation of hydroxides evident from field-emission scanning electron microscopy micrographs may limit further applications of harvested biomass. By adding 12 mg/L of alum or 4.8 mg/L of polyaluminium chloride, up to 36.6% and 40% of the initial biomass was harvested respectively at pH 6. Their poor performances were deduced to be the effect of buoyancy due to the long, curved needle-like structure with tapered ends of Ankistrodesmus. Remarkably, the use of 120 mg/L of autoclaved rice starch has enhanced the biomass recovery to at least 80%; improvement of 2 fold from those achieved using chemical coagulants. The bridging mechanism induced by the use of starches coupled with the effect of slow mixing has been found to be paramount for enhancing the floc formation process through effective linking of neighbouring cells. Subsequently, an extended blanket of Ankistrodesmus cells was formed which facilitated its heightened settling upon treatment with starches.